MODIFIKASI PERMAINAN TRADISIONAL PRESEAN TINGKAT SEKOLAH DASAR DI SD ISLAM NW TANAH ABROR - Hendra, Hendra -; Afrian, Herman -; Suryansah, Suryansah - (Universitas Hamzanwadi, 2019)
This research aim to to yield traditional game modification of peresean of good elementary school storey; level, pleasant and effective able to be used by physical education teacher. This research represent research of development (development and research education (R D) covering as follows: (1) product development; ( 2) gathering of information; ( 3) product desain ( model draft); ( 4) expert validasi and revise; ( 5) small scale field test-drive and revise; ( 6) big scale field test-drive and revise; (7) making of final product, revise small scale test-drive at 10 Elementary Sekolah Dasar Islam NW Tanah Abror; (8) big scale product test-drive at 20 Elementary Sekolah Dasar Islam NW Tanah Abror; (9) reviseing and product . Instrument that is: (1) Sheet interview and kuesioner. Technique analyse data that is descriptive analysis qualitative and is quantitative. Result of this research in the form of traditional game modification of peresean. Result indicate that modification game of traditional athletics of peresean for elementary school in Elementary Sekolah Dasar Islam NW Tanah Abror effective and good direspon. This matter is proved by percentage, average value at expert kuesioner is 66% at small scorpion test-drive, 73% at big scale and positive educative participant respon so that can be used in study.